Changes in abiotic dissipation rates and bound fractions of antibiotics in biochar-amended soil. (20th May 2020) - Zhang, Guixiang; Zhao, Zhihua; Zhu, Yuen
Abstract: To understand the impacts of molecular structures and biochar types on abiotic dissipation and bound fractions of antibiotics in soil, nine biochar types were applied into a soil contaminated with 16 antibiotics. In soil without biochar, the abiotic dissipation rates of antibiotics were generally tetracyclines (TCs) > sulfonamides (SAs) > quinolones (QLs). The trend was quite consistent with the total amounts of oxygen (O), nitrogen (N) and/or sulphur (S) atoms in antibiotic molecular structures. The dissipation trends of TCs (excluding oxytetracycline) and QLs (excluding ofloxacin) were just opposite the order of their logKow values, indicating that hydrophobic adsorption played the key role in their abiotic dissipation. The reason why oxytetracycline and ofloxacin were unique is they had one more O-containing functional group, when compared with the other TCs and QLs, respectively, resulting in their different hydrophobic adsorption affinities. For SAs, sulfadiazine and sulfachinoxalin had the highest and lowest abiotic dissipation rates, respectively. QLs and TCs were the dominant tightly bound fractions, while molecular structures influenced the bound fractions of SAs. In biochar-treated soils, biochars produced at 250 °C generally had a positive effect on the abiotic dissipation rates of antibiotics. The effect sizes of biochars produced at 400 °C and 600 °C for the abiotic dissipation of antibiotics were influenced by both biochar type and antibiotic molecular structure. Biochar type had the strongest impact on SA bound fractions, followed by TCs, while it had minimal influence on QLs. Biochars generally decreased the apparent distribution coefficients (Kapp ) of antibiotics in soil, indicating an increase in antibiotic leaching following biochar addition. Graphical abstract: Image 1 Highlights: Abiotic dissipation rates of antibiotics in soil were molecular structure-depended. Biochar produced at 250 °C generally enhanced the abiotic dissipation of antibiotics. Biochar had the strongest impact on bound fractions of sulfonamides. Biochar generally reduced apparent distribution coefficients of antibiotics in soil. Attention should be paid to the increased antibiotic leaching in biochar-treated soil.